Design and Implementation of a Smart Campus Flexible Internet of Things Architecture on a Brazilian University - Bruno Oliveira Zarpellon; Luis de Oro Arenas; Eduardo Paciencia Godoy; Fernando Pinhabel Marafao; Helmo K. Morales Paredes (IEEE Access)
This work proposes a flexible and comprehensive Internet of Things (IoT) architecture designed for application on smart campuses to build their smart infrastructure and facilitate their transition to becoming smart. The concept of a smart campus is derived from the concept of a smart city, which was developed to demonstrate how urban areas were addressing their new and dynamic challenges by integrating technology and data-driven decision-making. Although the concept of the smart campus was initially conceived to study the smart city in a less complex setting, over time, both concepts have evolved into distinct areas of inquiry, exhibiting unique characteristics and impacts. In general, a smart campus is a university campus where information and communication technologies and IoT are applied to some or all the campus processes, thereby making these processes more efficient, cost-effective and environmentally sustainable for the institution, its members and the surrounding community. Additionally to presenting the proposal for a flexible and comprehensive architecture for a smart campus, this paper also demonstrates its interpretation for implementation on a Brazilian campus transitioning to become smart, the Institute of Science and Technology, Sorocaba (ICTS) - campus of the São Paulo State University (Unesp) in Sorocaba, Brazil. To the best of the authors’ knowledge, there is a scarcity of existing works which address this level of detail when proposing an IoT architecture for a smart campus. The implementation of this architecture has demonstrated that it can be successfully deployed using only open-source technologies. Furthermore, it has been shown that anyone with access to the campus website can access most of the data collected and stored on the system.